2013
DOI: 10.1007/s11199-012-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of the MD: The Impact of Role Models, Identity Compatibility, and Belonging Among Undergraduate Women

Abstract: Women continue to face gender-related challenges in the medical field in places around the world where it has traditionally been male-dominated, including in the U.S. In an online experimental study with women attending a mid-sized public university in the Northeastern U.S. (N= 55) who were interested in pursuing a pre-medical track (being pre-med) as undergraduates, we explored the mechanisms involved in undergraduate women’s pursuit of a career as a physician, focusing on three factors: exposure to successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 49 publications
(91 reference statements)
6
94
1
1
Order By: Relevance
“…Although the gender-gap has narrowed in the medical field (Rosenthal, Levy, London, Lobel, & Bazile, 2013), a pattern of horizontal and vertical gender segregation tends to prevail (Miller & Clark, 2008;Riska, 2011;Rosende, 2002), with persisting and substantial asymmetries between men and women. Research conducted in several countries (e.g., Lapeyre & Le Feuvre 2005;Linehan et al, 2013;Rosende, 2008;Rosenthal et al, 2013) shows that women continue to experience substantial disadvantages in comparison to men, and to work more in part time, while men occupy the higher status positions and are better paid (Lo Sasso, Richards, Chou, & Gerber, 2011), even in what might be deemed female specializations such as pediatrics (Machado, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the gender-gap has narrowed in the medical field (Rosenthal, Levy, London, Lobel, & Bazile, 2013), a pattern of horizontal and vertical gender segregation tends to prevail (Miller & Clark, 2008;Riska, 2011;Rosende, 2002), with persisting and substantial asymmetries between men and women. Research conducted in several countries (e.g., Lapeyre & Le Feuvre 2005;Linehan et al, 2013;Rosende, 2008;Rosenthal et al, 2013) shows that women continue to experience substantial disadvantages in comparison to men, and to work more in part time, while men occupy the higher status positions and are better paid (Lo Sasso, Richards, Chou, & Gerber, 2011), even in what might be deemed female specializations such as pediatrics (Machado, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in several countries (e.g., Lapeyre & Le Feuvre 2005;Linehan et al, 2013;Rosende, 2008;Rosenthal et al, 2013) shows that women continue to experience substantial disadvantages in comparison to men, and to work more in part time, while men occupy the higher status positions and are better paid (Lo Sasso, Richards, Chou, & Gerber, 2011), even in what might be deemed female specializations such as pediatrics (Machado, 2003). Moreover, the reconfiguration of segregation extends to countries with more balanced gender distributions in the medical field such as Russia, Finland, Britain and Sweden (Rosende, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is not consistent with literature in other health care fields (Inglehart et al, 2014;Rosenthal, Levy, London, Lobel, & Bazile, 2013), as well as science, technology, engineering, and mathematics fields (Dabneya et al, 2012;Kaye, Bems, Cress, & Nazar, 2014;Sadler, Sonnert, Hazari, & Tai, 2012). Research in these fields has em phasized mentoring relationships in undergraduate and even high school education.…”
Section: Mentors and Role Modelsmentioning
confidence: 60%
“…Multiple studies have indicated that students who feel like they belong on campus are more likely to have a positive experience (Chemers, Hu, & Garcia, 2001;Hurtado & Carter, 1997;Leese, 2010;London, Rosenthal, Levy, & Lobel, 2011;Sylvia Hurtado, Griffin, Arellano, & Cuellar, 2008). This work contributes to the emerging SBP by demonstrating that geographic methodologies, specifically studies of place, can contribute to research on the development, or lack of development, of student sense of belonging, an area that has primarily been addressed by psychologists (Cheryan, Plaut, Davies, & Steele, 2009;Good, Rattan, & Dweck, 2012;Rosenthal, Levy, London, Lobel, & Bazile, 2013;Stout, Dasgupta, Hunsinger, & McManus, 2011). Additionally, this approach can be replicated and compared across different campus environments and among different communities.…”
Section: Introductionmentioning
confidence: 94%